The Effect of Ketoconazole and Quinestrol Combination on Reproductive Physiology in Male Mice - Yu Ji; Yujie Wang; Yuhang Liu; Yutong Liu; Jiao Qin; Daohuan Yuan; Quansheng Liu (Animals)
This study investigates whether ketoconazole, a CYP3A4 inhibitor, can enhance the suppressive effects of quinestrol on reproductive capacity, potentially allowing for a reduced quinestrol dosage while maintaining its efficacy. A total of 104 healthy adult male mice were divided into two groups, assessed at 10 and 30 days. Within each group, six treatment categories were tested: the control (CK), quinestrol alone (Q1, Q5), and quinestrol combined with varying doses of ketoconazole (Q1 + K0.4, Q1 + K2, Q5 + K0.4). The key parameters measured included internal and reproductive organ weights, sperm density, sperm motility, sperm abnormalities, and CYP3A4 enzyme content in intestinal and liver tissues. After 10 days, the combination of a low dose of quinestrol with ketoconazole (Q1 + K0.4) showed the most significant pronounced effects in reducing reproductive potential, with notable reductions in epididymal weight, sperm density, sperm abnormality rate and vitality, serum hormone levels, and CYP3A4 content in the small intestine and liver. Although some reproductive parameters returned to near-baseline levels after 30 days, the Q1 + K0.4 regimen continued to exhibit reduced seminal vesicle weight and testosterone levels. Importantly, the combination did not significantly increase CYP3A4 enzyme content, indicating effective metabolic inhibition. The combination of quinestrol and ketoconazole, especially the Q1 + K0.4 regimen, demonstrated the most noticeable impact on reducing reproductive capacity. This regimen significantly reduced key reproductive parameters and showed strong metabolic inhibition, suggesting that ketoconazole substantially enhances the efficacy of quinestrol in fertility control.